Rules of electronic data in criminal cases in China - Yang, Fan (International journal of law, crime and justice, 2021)
As the core evidence in the Internet era, electronic data has been readily incorporated into criminal proceedings. In China, it was not until the Criminal Procedure Law was amended in 2012 that electronic data was classified as an independent type of evidence. Apart from the Criminal Procedure Law, there are three main regulations pertaining to the use of electronic data. Even though great endeavors have been made by Chinese authorities to integrate novel technologies into electronic data and the basic framework for the regulations of electronic data has been formed, there are still some lingering weaknesses in the current regulations: vulnerable rights of criminal suspects, the absence of the special investigation department, unclear provisions in relevant regulations, and improper remedy mechanisms. To further develop the rules of electronic data, China is supposed to place emphasis on the idea of rights protection and the interaction between new technologies and evidence theory.